A novel splice-site mutation of the HNF1B gene in a family with maturity onset diabetes of the young type 5 (MODY5). (23rd September 2020) - Fujita, Yuki; Tanaka, Daisuke; Tatsuoka, Hisato; Matsubara, Miho; Hyo, Takanori; Hamamoto, Yoshiyuki; Komiya, Toshiyuki; Inagaki, Nobuya; Seino, Yutaka; Yamazaki, Yuji
Abstract : Summary: Maturity-onset diabetes of the young (MODY) is a form of monogenic diabetes mellitus characterised by early onset and dominant inheritance. Delayed diagnosis or misdiagnosis as type 1 or type 2 diabetes mellitus is common. Definitive genetic diagnosis is essential for appropriate treatment of patients with MODY. The hepatocyte nuclear factor 1-beta (HNF1B) gene is responsible for MODY type 5 (MODY5), which has distinctive clinical features including renal disease. MODY5 should always be considered by clinicians in patients with early onset diabetes and renal anomalies. We report a case of a 30-year-old Japanese male with early-onset diabetes mellitus, renal anomalies and family history of diabetes that was suggestive of MODY5. Renal histology showed no evidence of diabetic nephropathy. Genetic testing revealed a novel heterozygous splice-site mutation of the HNF1B gene in the family members. It was strongly suggested that the mutation could underlie our patient's MODY5. Learning points: Genetic diagnosis of MODY is relevant for appropriate treatment. Dominantly inherited early-onset diabetes mellitus with renal cysts suggests MODY5. Scanning the non-coding regions is important for not missing a mutation in HNF1B.